CHOLINESTERASE INHIBITING INSECTICIDES (PARATHION)—Chemical and Clinical Aspects - Thompson, James H. (1955)
Since parathion and other cholinesterase insecticides are being used extensively, safety precautions are important, and the need for prompt and adequate therapy if poisoning does occur must be emphasized. This paper stresses the acute nature of the poisoning and attempts to outline the basic principles of therapy so that practicing physicians may handle cases with more confidence, which should help prevent prolonged periods of functional disturbances due to anxiety following poisoning.